CONVERSATIONAL ANALYSIS OF SELLING-BUYING IN DOLOK SANGGUL TRADITIONAL MARKET - RAYA FITRI MANALU; FAUZIAH KHAIRANI LUBIS; ANNA RIANA SURYANTI TAMBUNAN (State University of Medan, 2021)
The thesis deals with conversational analysis of selling-buying in DolokSanggul traditional market. The objectives of this study were to find out types and most dominant type of turn-taking used in Batak Toba Seller and buyers in DolokSanggul Traditional market. The study was conducted by using desccriptive qualitative method. The data of the study were conversation and interaction between sellers and buyers during the selling-buying process. The data of this study contained 25 conversations. The data analysis were taken by listing and tabulating the data. The data were analyzed based on the theory that proposed by Sack et al (1974) . The findings inducted that there were three types of turn-taking found in Doloksanggul Traditional market . The finding were showed that CS2TNS (48%) SS (20%) and SCS (32%) and the most frequent turn-taking occurred in the conversation among seller and buyer is Current Speaker Select the Next Speaker (C2TNS). The conversation described how participant organize their interaction by distributing turns to the speakers. The transition from turn to next with no gap and no overlap are common occurred.